Role of epithelial hyperplasia in regression following photorefractive keratectomy. - Gauthier, C. A. (1996)
AIM--To determine the relation between epithelial hyperplasia and regression of effect after photorefractive keratectomy (PRK). METHODS--Seventy unilaterally treated patients with PRK were examined. All eyes had been treated with the Summit excimer laser 27 (SD 7) months previously with zone diameters of 4.1 to 5.0 mm. The untreated fellow eyes served as controls. Epithelial thickness was measured centrally with a thin slit optical pachometer and manifest subjective refraction was performed. RESULTS--The epithelium was 21% thicker in the treated eye (p < 0.0001). The relation between refractive regression and epithelial hyperplasia was significant (r = 0.41; p < 0.001). CONCLUSIONS--Epithelial hyperplasia after PRK correlated with the myopic shift (including hyperopia reduction) after treatment with the Summit laser. A model is proposed suggesting that both subepithelial and epithelial layers contribute to regression in the Summit treated eyes with 18 microns of epithelial hyperplasia contributing each dioptre of regression.